A Study on Mango Economy of Malda District, West Bengal - Siddiqui, Shamsul Haque; Aktar, Nasim; Sultana, Chand (National Geographical Journal of India, 2022)
Mango is called “the king of all fruits” on account of its nutritive value, taste, attractive fragrance and health promoting qualities. Malda, district of West Bengal, popularly known as ‘Mango city’ not only in the State but all over India due to its varieties. The present study is deals with two parts. First part deals with the block-wise growth pattern in terms of area, production and yield of mango which increased during 1990-91 to 2010-11. The compound annual growth rate of area, production and yield of mango is 1.18 %, 5.92 % and 4.69 % respectively. The second part is an attempt to understand the inter-linkages between the stakeholders and the role of aratdars (middlemen) in marketing channels where all the profits consumed by the aratdars (middlemen) or traders than the growers. Therefore, the farmers did not get the actual value of mango. Mechanization, diversification and commercialization of agriculture resulted in shifting of cropping pattern from traditional crops to new crops, which had contributed to the increased area and production under mango in the study region. Changing demand pattern also contributed significantly to shifting of more area under production of mango.